Effect of Recreational Futsal on Body Composition in Passive Football Players - Arben Maliqi; Blerim Sylejmani; Nazim Myrtaj (OVS LLC, 2022)
The purpose of this study was to evaluate the impact of recreational futsal on passive middle-aged footballers in body composition.  Materials and methods. The research was conducted on a sample of 58 men aged from 30 to 40, average age 35.88 ± 2.39. The sample was divided into two groups. The first group included 29 passive football players (average age 35.58 ± 2.36) who were engaged in recreational futsal 2-3 times a week, and the second group included 29 passive football players (average age 36.17 ± 2.42) who weren't engaged in recreational physical activity. The body composition was assessed by TANITA BC-601, the method of bioelectrical impedance, which became a reference method in research studies in the body composition analysis. The variables obtained were: body height (cm), body weight (kg), fat mass (%), muscle mass (kg), bone mass (kg), body mass index (kg/m2), calorie consumption - daily calorie intake (kcal), vitality of the body, quantity of water in the body (%), visceral fat (%). Results. Groups are not distinguished in the variables body height (HBH), calorie consumption - daily calorie intake (DCI), vitality of the body (BMR), and quantity of water in the body (TBV) because p > 0.05. In the variables where body mass, body fat tissue and muscle mass were assed, namely body weight (BWT), fat mass (BFP), muscle mass (TBM), bone mass (BMD), body mass index (BMI) and visceral fat (AVF), a statistically significant difference was gained p < 0.05 in favor of the group of passive football players who were involved in recreational futsal. Conclusions. It can be said that the recreational futsal as physical activity is an effective tool to improve body composition not only in passive football players but in all persons of all ages regardless of gender. Intensity and duration in recreational futsal is an effective way to reduce body fat in the population of passive middle-aged football players.